International Law Foundations of Regional Integration in the European Union. Experience of the Austrian Republic - Anatoliy V. Pronin (Московский журнал международного права, 2014)
It is objected in the text that federative entities may be determined as subjects of international law. Legal component of the European Union regional policy, when Euroregions connected by economical but not political reasons were created, was also analyzed on the example of the Austrian Republic. Cases of the international treaties and European Union secondary law implementation on the level of the Austrian federal lands were also put in the article. Attention was also paid to the cases of federal lands non- feasibility in questions of international and European law implementation and to the system of legal mechanisms which were created to escape this lack of action.